1998
DOI: 10.1097/00002371-199811000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of HLA DRB1 and DQB 1 Polymorphism in Italian Melanoma Patients

Abstract: Several studies have reported association between a variety of malignancies and human leukocyte antigens (HLA) genes. However, conflicting data have been reported on HLA association and melanoma. We report here serologic and molecular analysis by polymerase chain reaction sequence-specific primers (PCR-SSP) and PCR sequence-specific oligonucleotides (PCR-SSO) of HLA class I1 DRBl and DQB 1 loci in 132 patients with melanoma and 102 ethnically matched controls. Molecular typing of DQB 1 polymorphism showed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 2 publications
2
24
0
Order By: Relevance
“…Negative associations were found between DQB1*0302/0303 and CMM, whereas a positive association was found for DQB1*0501 in two Italian studies. 99,100 In Japanese patients with CMM, a positive association was found with DQB1*0302, whereas negative associations were reported for DRB1*0802 and DQA1*0101/ 0104/0401. 101 Finally, in a British population, an increase in the frequency of DQB1*0303 was found among CMM patients.…”
Section: Immune-related Genesmentioning
confidence: 95%
See 1 more Smart Citation
“…Negative associations were found between DQB1*0302/0303 and CMM, whereas a positive association was found for DQB1*0501 in two Italian studies. 99,100 In Japanese patients with CMM, a positive association was found with DQB1*0302, whereas negative associations were reported for DRB1*0802 and DQA1*0101/ 0104/0401. 101 Finally, in a British population, an increase in the frequency of DQB1*0303 was found among CMM patients.…”
Section: Immune-related Genesmentioning
confidence: 95%
“…94 A variety of other studies have reported even more conflicting results with HLA-DQB1*0301 among CMM populations. One study reported no association between DQB1*0301 and risk of CMM, 98 whereas another found a slight, but not significant, positive association with susceptibility, 99 and yet another indicated a negative association with risk of CMM. 100 The variability of these results could, in part, be due to sample size, patient series heterogeneity, control populations, or technical differences in detecting HLA genotype.…”
Section: Immune-related Genesmentioning
confidence: 96%
“…However, conflicting data have been reported on HLA association and melanoma (1)(2)(3)(4)(5)(6)(7)(8). The presence of DQB1*0301 (1, 2) and DRB1*1101 (3) has been reported to be associated with the progression of the disease in Caucasians, and it has been reported that HLA-DQB1*0303 and DQB1*0301 can influence susceptibility and prognosis in British patients with melanoma (4).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, several studies have examined the involvement of the HLA system in the aetiology of malignant melanoma, 1–11 and it has been speculated that HLA class II association might be the immunogenetic basis for melanoma susceptibility 1 . However, reports have not shown consistent results perhaps because of sample size, patient series heterogeneity, the choice of control populations and differences in the techniques employed for the detection of HLA antigens or alleles.…”
mentioning
confidence: 99%